Alarm Clock-Based Reminder for Improving Low Adherence on Option B Plus Antiretroviral Therapy Among HIV Positive Pregnant and Lactating Mothers in Northern Ethiopia - Gebretsadik GG (Dove Medical Press, 2020)
Gebremedhin Gebreegziabher Gebretsadik,1 Hailay Gebretnsae,2 Mulu Ftwi,1 Afewerki Tesfahunegn3 1Department of Midwifery, College of Health Science, Adigrat University, Adigrat, Tigray, Ethiopia; 2Tigray Health Research Institute, Mekelle, Tigray, Ethiopia; 3Department of Epidemiology, College of Health Science, Mekelle University, Mekelle, Tigray, EthiopiaCorrespondence: Gebremedhin Gebreegziabher Gebretsadik Email gebremedhingebretsad@gmail.comBackground: Option B plus antiretroviral therapy (ART) is an approach used to eliminate new Human Immune Deficiency Virus (HIV) infections among infants. Considering the high adherence on Option B plus ART in HIV positive mothers is a crucial part in preventing mother-to-child transmission HIV. Therefore, this study was performed to assess the status of adherence and factors related to Option B plus ART.Methods: A cross-sectional study design was conducted in Eastern zone of Tigrai Region from January to February 2017. Data were collected by using pre-tested structured interviewer-administered questionnaire from 350 participants selected using simple random sampling. Descriptive and binary logistic regression was done during analysis.Results: The overall good adherence status of Option B plus ART among pregnant and lactating mothers was  67.3% [62.3– 72.3%]. Attending formal education (AOR=2.78, 95% CI 1.52– 5.07), traveling for < 1 hour to reach health facility (AOR=2.03, 95% CI 1.19– 3.44), (CD4) count < 350 cells/mm3 (AOR=2.3, 95% CI 1.33– 3.95), starting their Option B plus during pregnancy (AOR= 2.08, 95% CI 1.08– 3.97), taking one pill per day (AOR=2.12, 95% CI 1.25– 3.58), using a clock as a reminder (AOR=2.51, 95% CI 1.3– 4.86), and having good male involvement (AOR=2.91, 95% CI 1.64– 5.16) were associated with good level of adherence for Option B plus ART treatment.Conclusion: Our study revealed that the level of good adherence is low compared with the national target. Therefore, addressing the low adherence of Option B plus ART requires a policy response, such as efforts to enhance male partner involvement and better service accessibility in Prevention of Mother-to-Child Transmission (PMTCT) program. Moreover, health care providers and policymakers need to maximaze their efforts on HIV positive pregnant and lactating mothers using a clock as a reminder.Keywords: adherence, Option B plus ART, Prevention of Mother-to-Child Transmission program; PMTCT, Ethiopia